Training methods and considerations for practitioners to reduce inter-limb asymmetries - Bishop, C.; Turner, A.; Read, P. (Strength and Conditioning Journal, 2018)
Inter-limb asymmetries have been a common source of investigation in recent years with the majority of studies highlighting its prevalence in a range of athletic tasks. Few have tested whether reducing inter-limb differences are required for improved physical performance. Furthermore, there are a number of considerations that may exist which practitioners should consider prior to starting training interventions to reduce these differences. This article will discuss the available body of literature pertaining to the reduction of inter-limb asymmetries to date and provide example training programs to show how they can be addressed if their reduction is deemed necessary.